Response of lotic microbial communities to altered water source and nutritional state in a glaciated alpine floodplain. (3rd May 2013) - Freimann, Remo; Bürgmann, Helmut; Findlay, Stuart E. G.; Robinson, Christopher T.
Abstract : Factors driving bacterial community composition (BCC) and linkages to ecosystem function (EF) are a fundamental interest in microbial ecology. Climate warming is expected to cause a shift from glacial‐ to groundwater‐dominated water sources in alpine catchments due to receding glaciers, which is likely accompanied by a shift in BCC and EF. In this context, we performed a reciprocal transplant experiment of hyporheic sediments within a Swiss alpine floodplain. We assessed the influence of water source (groundwater = krenal, glacial water = kryal) and nutritional state (C, N, and P) on BCC and EF. Experimental response was tested using automated ribosomal intergenic spacer amplification and potential activities of eight different enzymes. BCC from both kryal and krenal systems was highly resistant to changes in water source, yet exhibited pronounced EF flexibility. Major factors determining BCC and EF response were sediment origin followed by seasonal variation in BCC. The gradient in seasonal change in BCC showed different strengths in the two water systems. Krenal BCC was more seasonally stable compared with kryal BCC, although functional plasticity showed the same extent in both. This difference in connectivity between BCC and EF suggests that krenal BCC was dominated by generalists, whereas kryal BCC was dominated by specialists. The weak effect of altered nutritional state on BCC and EF indicates a complex but hierarchically structured relationship among these factors. We conclude that microbial communities in alpine catchments are able to rapidly buffer the effect of shifts in water source on ecosystem functioning.